A Review of the Cytokine IL-17 in Ocular Surface and Corneal Disease. (2nd January 2019) - Garbutcheon-Singh, K. B.; Carnt, N.; Pattamatta, U.; Samarawickrama, C.; White, A.; Calder, V.
ABSTRACT: Aim: To investigate the role of interleukin-17 in ocular surface and corneal disease. Ocular surface and corneal disease is a leading cause of blindness and is an ongoing challenge for the public health sector to implement effective therapies. The majority of cells in corneal lesions are derived primarily from neutrophils that induce inflammatory events that lead to tissue damage. One of the key pro-inflammatory cytokines is IL-17, and it has been investigated in order to facilitate the understanding of the pathogenesis of ocular surface lesion development. Method: A review of the literature was performed through a systematic approach. Results: IL-17 has been shown to exacerbate dry eye disease, viral and bacterial keratitis lesion severity, although it was found to be protective for Acanthamoeba. Antibodies developed to neutralize IL-17 have shown some promise in reducing the severity of some diseases. Conclusion: IL-17 plays a role in the pathogenesis of ocular surface and corneal disease and targeting this cytokine may provide a useful treatment option in the future.